High resolution geochemical investigation of the bivalve shells (Glycymeris sp.) from shell mounds in Jeju Island, Korea: Late Holocene paleoclimatic implications related to East Asian Monsoon climate. (21st January 2016) - Kim, J.S.; Woo, K.S.; Hong, W.
Abstract: Recent and shell mound bivalves ( Glycymeris sp.) were collected from two sites (Sangmori and Udo, Jeju Island) to investigate paleoceanographic conditions using high resolution stable isotope and trace element data. The radiocarbon ages are about 3210 ± 50 and 4210 ± 60 BP for the Sangmori and Udo shell mounds, respectively. Both oxygen and carbon isotopic compositions of the shell mound bivalve shells show clear seasonal cycles with depleted values during summer and the coeval trend, which indicates that they were controlled by freshwater input. Similar ranges of both isotopes indicate that shallow seawater conditions near the Sangmori and Udo shell mounds are more or less similar. However, more negative oxygen and carbon isotope values of the shell mound bivalves than the recent counterpart suggest that surface seawater salinity near Jeju Island was lower due to the increase in Changjiang River Discharge. Mg contents of the recent bivalve reflect surface seawater temperature changes whereas Sr and Ba contents were controlled by nutrient concentrations directly influenced by Changjiang River Discharge. Geochemical data of the recent and shell mound bivalves may imply higher precipitation (more intense East Asian Summer Monsoon activity) at ∼3.2 and 4.2 ka under the influence of the terminal stage of Holocene climatic optimum in south China or may reflect smaller fluctuating peaks during its decline.